Our freedom struggle (history and civics) - standard five - Shinde, Bapusaheb; Wagh, Dattatray; Kulkarni, Sadhana; Begampure, Chandrashekhar (Maharashtra State Bureau of Textbook Production and Curriculum Research, 2006)
Preface: "The "Primary Education Curriculum - 2004" was prepared in the State of Maharashtra following the "National Curriculum Framework - 2000". This syllabus is being implemented serially from the academic year 2006 - 2007. The syllabus includes History and Civics Std III onwards."